1999
DOI: 10.1111/j.1469-7793.1999.0757u.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid block of protein kinase C signalling in mouse pituitary corticotroph AtT20 D16:16 cells

Abstract: The regulation of large conductance calcium‐ and voltage‐activated potassium (BK) currents by activation of the protein kinase C (PKC) and glucocorticoid signalling pathways was investigated in AtT20 D16:16 clonal mouse anterior pituitary corticotroph cells. Maximal activation of PKC using the phorbol esters, 4β‐phorbol 12‐myristate, 13‐acetate (PMA), phorbol 12, 13 dibutyrate (PDBu) and 12‐deoxyphorbol 13‐phenylacetate (dPPA) elicited a rapid, and sustained, inhibition of the outward steady‐state voltage‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…In contrast to iberiotoxin, PMA is not a classical pharmacological tool to study BK channels. The action of PMA is variable, ranging from channel activation (6) to inhibition (46), depending on the cell type. The reported effects were not associated with a rise in [Ca 2ϩ ] i but, rather, with PKC-dependent protein phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to iberiotoxin, PMA is not a classical pharmacological tool to study BK channels. The action of PMA is variable, ranging from channel activation (6) to inhibition (46), depending on the cell type. The reported effects were not associated with a rise in [Ca 2ϩ ] i but, rather, with PKC-dependent protein phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of PMA, a well-known PKC activator (39), on BK channel activity are not clear: inhibition (46) and activation have been reported (6). Ahluwalia et al (1) found that PMA increased [Ca 2ϩ ] i in human neutrophils and, therefore, activated BK channels that are Ca 2ϩ sensitive.…”
Section: Membrane Currents In Human and Mouse Neutrophils Are Not Inhmentioning
confidence: 99%
“…In these cells, glucocorticoids rapidly activate BK channels via a nongenomic mechanism (195). Glucocorticoids applied for 2 h also promote de novo BK mRNA and protein synthesis and antagonize PKA-and PKC-dependent inhibition of BK channels (188,196). Further studies revealed that glucocorticoid regulation of BK channels in these cells is mediated by serine/ threonine protein phosphatase (197) and that alternative splicing determines sensitivity of BK channels to glucocorticoids and switches their sensitivity to protein phosphorylation (198,199).…”
Section: Calcium-activated K ؉ Channelsmentioning
confidence: 94%
“…For example, adrenal steroids downregulate BK channel currents in hippocampal neurons (Kerr et al, 1989) and can mediate the inclusion of the stress axis regulated exon (STREX) in adrenal chromaffin cells (Shipston et al, 1996;Xie and McCobb, 1998;Tian et al, 1999). Fluctuations in estrogen and/or progesterone during pregnancy may influence alternative exon splicing in mouse uterine muscle, altering muscle contractility (Benkusky et al, 2000).…”
Section: Steroid Hormone Modulation Of Ion Channel Gene Expressionmentioning
confidence: 99%